2020
DOI: 10.21595/jve.2019.20523
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of train-induced vibrations on nearby high-rise buildings by open or geofoam-filled trenches

Abstract: The vibrations induced by moving trains especially in close distances with high-rise buildings can be destructive. The high technology of wilding rails induced a high train velocity which is associated with high vibrations. The buildings near the railways suffer from the train-induced vibrations. In this paper, a 3D FEM model was constructed to study the train-induced vibrations on a nearby high-rise building (HRB), show its response and investigate the most suitable technique to mitigate the effect of the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
0
4
0
1
Order By: Relevance
“…Some frequent causes are due to the vibrations and the subsequent loss of the bearing capacity of the affected soils during excavation [8,9]. Vibrations due to vehicular traffic or by railways can appear [10][11][12], and this can also propagate through tunnels in the operation stage [13].…”
Section: Introductionmentioning
confidence: 99%
“…Some frequent causes are due to the vibrations and the subsequent loss of the bearing capacity of the affected soils during excavation [8,9]. Vibrations due to vehicular traffic or by railways can appear [10][11][12], and this can also propagate through tunnels in the operation stage [13].…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al [11] found that the vibration isolation performance of the open trench-wave impedance block barrier system can reduce the vibration generated by a vibration source. 3D FEM model was constructed by Kontoni et al [12] to study the train-induced vibrations on a nearby high-rise building. The attenuation response from a series of block vibration tests performed on a model square machine foundation at a site near IIT Kanpur, India, is studied by Surapreddi et al [13].…”
Section: Introductionmentioning
confidence: 99%
“…The damping ditch can reduce the impact of blasting stress waves on the adjacent structures while ensuring that the construction progress remains unchanged. Many researchers have conducted a lot of studies on the blasting vibration attenuation model and on vibration isolation method intended for providing the damping effect [7][8][9]. Jayawardana et al [10] investigated the effects of dual in-filled trenches with different geometry on mitigating ground vibration using the finite element method, and then presented an evaluation and prediction method of vibration mitigation using an artificial intelligence neural network.…”
Section: Introductionmentioning
confidence: 99%